IoT Based Paint Feed Process Monitoring System Implementation - Shahrul; Arie Budiansyah; Suryadi; Rudi Arif Candra; Dirja Nur Ilham (ITScience (Information Technology and Science), 2022)
The increasing level of human mobility causes pets to be abandoned because humans have activities that cannot be left behind or work that must always be done, with this, pets, one of which is a cat, are often hungry because the caregiver is busy working and does not have time to feed the cat. This research is about designing an automatic cat feeder with a periodic monitoring system with a Nodemcu control system with two sensors, namely an Ir sensor and an Ultrasonic sensor with a telegram notification output. the working principle of the Sensors Ir 1 and 2 will detect a cat, if it hits the cat, the place for giving food and drink will open automatically while ultrasonic sensors 1 and 2 are for monitoring food and drink if food and drink do not hit the ultrasonic sensor it will enter a notification that the food and drink had run out. the conclusion of making this tool is to make it easier for cat owners to automatically feed cats.